2017
DOI: 10.1053/j.gastro.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Cardiovascular Disease Risk in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Background & Aims Cardiovascular disease (CVD) is the leading cause of death among patients with non-alcoholic fatty liver disease (NAFLD). Moderate drinking (vs abstinence) is associated with lower risk of CVD in the general population. We assessed whether alcohol use is associated with CVD risk in patients with NAFLD. Methods We analyzed data from participants in the Coronary Artery Risk Development in Young Adults longitudinal cohort study of 5115 black and white young adults, 18–30 years old, recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 57 publications
(63 reference statements)
0
38
0
1
Order By: Relevance
“…95 However, the association between alcohol and reduced cardiovascular risk may be limited by residual confounding. In fact, a recent study that prospectively assessed alcohol consumption over time found no association between alcohol use and the presence of cardiovascular risk factors or subclinical cardiovascular disease, 98 although this study did not analyze clinical cardiovascular events. A recent analysis of individual participant data of 599,912 current drinkers in 83 prospective studies assessing risk thresholds for alcohol consumption 99 concluded that the threshold for lowest risk of all-cause mortality was 100 g ethanol per week.…”
Section: Extrahepatic Outcomesmentioning
confidence: 85%
“…95 However, the association between alcohol and reduced cardiovascular risk may be limited by residual confounding. In fact, a recent study that prospectively assessed alcohol consumption over time found no association between alcohol use and the presence of cardiovascular risk factors or subclinical cardiovascular disease, 98 although this study did not analyze clinical cardiovascular events. A recent analysis of individual participant data of 599,912 current drinkers in 83 prospective studies assessing risk thresholds for alcohol consumption 99 concluded that the threshold for lowest risk of all-cause mortality was 100 g ethanol per week.…”
Section: Extrahepatic Outcomesmentioning
confidence: 85%
“…A recent study in NAFLD patients with prospectively assessed alcohol consumption over time found no association between low alcohol use and the presence of cardiovascular risk factors or subclinical cardiovascular disease (VanWagner et al, ).…”
Section: Extrahepatic Outcomes In Nafldmentioning
confidence: 99%
“…(45) This is in contrast with a more recent study with prospectively assessed alcohol consumption over time, which found no association between alcohol use and the presence of CVD risk factors or subclinical CVD. (46) Nonetheless, clinical CVD events were not analyzed.…”
Section: Previous Studies On Nonhepatic Outcomesmentioning
confidence: 99%